Enhanced 808 nm driven Ce3+ doped red-emitting upconversion nanocrystals by intercalated nanostructures. Issue 22 (29th April 2016) - Shen, Ji-Wei; Lu, Junliang; Tu, Jun; Ouyang, Xiangyuan; Li, Hua
Abstract : 808 nm driven intense red-emitting upconversion nanocrystals were constructed by intercalating NaYF4 :Yb/Ho/Ce, as shell, into Nd 3+ sensitized nanostructures to conquer the energy transfer barrier from the Nd 3+ shell to the Yb 3+ core in Ce 3+ doped core–shell–shell nanostructures. Abstract : We report the red but weak upconversion luminescence of core–shell–shell structured upconversion nanocrystals (NaYF4 :Yb/Ho/Ce@NaYF4 :Nd@NaYF4 ) under excitation at 808 nm due to high surface Ce 3+ concentration in core nanocrystals hindering the energy transfer from the Nd 3+ shell to the Yb 3+ core. 10.2-fold upconversion luminescence enhancement was achieved by conquering the negative effects of non-uniform Ce 3+ distribution phenomena on upconversion processes via intercalating NaYF4 :Yb/Ho/Ce, designed as the shell, into the Nd 3+ sensitized nanostructure (NaYF4 :Nd@NaYF4 :Yb/Ho/Ce@NaYF4 :Nd@NaYF4 :Yb/Ho/Ce@NaYF4 ). The intercalation nanostructured upconversion nanocrystals show intense red upconversion luminescence with a red-to-green ratio of 5.0. Bright red upconversion luminescence of the Ce 3+ doped intercalation nanostructured upconversion nanocrystals embedded in biological tissues can be visualized even at a depth of 5 mm illuminated by 808 nm laser light. High efficiency 808 nm driven red-emitting upconversion nanocrystals are promising for bio-applications.